Analysis of the living standards of the population in Kazakhstan in the context of assessing the potential for inclusive growth and creative diversification of the economy - Khussainova, Zh.S.; Yeskendir, N.N.; Kuttybaeva, N.B.; Assanova, M.K.; Abauova, G.M. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Abstract Object: Determine trends in changes in living standards, the structure of household income and expenses in the Republic of Kazakhstan in recent years (2016–2022) to identify the potential for inclusive growth and creative diversification of the domestic economy. Methods: The methods of statistical analysis, comparison and the method of tabular and graphical representation of data are used. Findings: The conducted research revealed the following conclusions: steady increasing trends in the observed seven-years dynamics of income and expenses of the population of Kazakhstan (from 2016 to 2022) have been identified. The hypothesis of uneven growth of incomes and expenditures of the population of Kazakhstan has been confirmed, with the rate of income growth outstripping the rate of expenditure growth. The refractive dynamics of elements in the structure of household incomes in Kazakhstan was found, expressed in a reversal of their trends, which gave reason to distinguish two stages in the monitored period within the framework of the study: until 2020, first, the stage of reducing the share of income received from active activity in the labor market and increasing the share of social transfers received, then starting from 2021, the stage increasing the share of income from employment and reducing the share of social benefits from the state. In the structure of monetary expenditures, there was also a stage of increased growth in expenditures on food products (2016–2020), in the last two years these expenditures began to decrease again, but so far remain at a higher level than at the beginning of the period under review. There is a differentiation of incomes in the regional context and a significant gap in the monetary expenditures of urban and rural households. In addition, there are significant differences in the income structure by region and in the context of “city/village”. Conclusions: When pursuing a policy of regulating incomes and improving the well-being of the population, both nationally and at the regional level, it is necessary to focus on the peculiarities of the formation of household incomes and the specifics of the distribution of monetary expenses. In addition to macroeconomic parameters, it is necessary to understand in the “people-centric” model of public administration the influence of policy measures on the components of the well-being of the population, which will make it possible to develop more “targeted” support and incentive measures aimed at reducing inequality of income and opportunities, developing consumer demand, and creating conditions for the growth of human capital in the country, for the inclusion of the innovation and activity potential of youth and the reserves of economic activity of older people. Sustainable improvement of the well-being of the population and economic growth in the context of the widespread paradigm of inclusive growth is achievable under conditions of socio-economic diversification of creative industries and activation of civil society and social partnerships, which is associated with an increase in the overall socio-economic indicators of internal reproduction. Inclusive economic growth in the Republic of Kazakhstan needs to build an integration model for the development of creative industries, including institutional and economic elements for involving young people and the elderly in economically active activities in creative industries. Additional information: The study was carried out within the framework of a project funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant №. AP14871023).
Инклюзивті өсу және экономиканы шығармашылық әртараптандыру әлеуетін бағалау тұрғысында Қазақстан халқының өмір сүру деңгейін талдау
Анализ параметров уровня жизни населения в Казахстане в контексте оценки потенциала инклюзивного роста и креативной диверсификации экономики
Keywords: standard of living; average per capita income of the population; average per capita expenditure of the population; creative economy; inclusive economic growth